2017
DOI: 10.1039/c7cc00242d
|View full text |Cite
|
Sign up to set email alerts
|

N-Doped porous graphitic carbon with multi-flaky shell hollow structure prepared using a green and ‘useful’ template of CaCO3 for VOC fast adsorption and small peptide enrichment

Abstract: High N-doped porous graphitic carbons (S-NPGCs) with multi-flaky shell hollow structure were prepared by using CaCO as a green/useful template. S-NPGCs exhibit very fast adsorption for toluene (31 times that of HKUST-1) and effectively selective enrichment of small peptides with high inhibitory activity of angiotensin converting enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…16 However, most existing methods for preparing nitrogen-doped carbon materials, e.g., the thermal decomposition of nitrogen-containing precursors over metals such as Fe, Co and Ni, lead to the presence of residual metal species or impurities in the synthesized carbons, which seriously degrade the ORR performance. [17][18][19][20] Several recent studies have shown that nitrogen-doped carbons can be prepared as an electrocatalyst material for ORR without any metal precursors. 21,22 Thus, metal-free materials, including nitrogen-doped carbons, have attracted growing interest as a catalyst material in recent years on account of their excellent ORR electrochemical properties, low cost, low side-reaction effects and good stability.…”
Section: Introductionmentioning
confidence: 99%
“…16 However, most existing methods for preparing nitrogen-doped carbon materials, e.g., the thermal decomposition of nitrogen-containing precursors over metals such as Fe, Co and Ni, lead to the presence of residual metal species or impurities in the synthesized carbons, which seriously degrade the ORR performance. [17][18][19][20] Several recent studies have shown that nitrogen-doped carbons can be prepared as an electrocatalyst material for ORR without any metal precursors. 21,22 Thus, metal-free materials, including nitrogen-doped carbons, have attracted growing interest as a catalyst material in recent years on account of their excellent ORR electrochemical properties, low cost, low side-reaction effects and good stability.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its unique physical and chemical properties, precipitated calcium carbonate is widely used in chemical [1][2][3], food [4], and pharmaceutical industries [5] and in other fields [6,7]. The properties of materials are determined by their structure, and the crystal type and the morphology are the important factors of materials' structure.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption and separation strategies using porous materials, such as affinity separation, magnetic separation, and porous adsorption, facilitate the rapid screening of peptides with specific activity from protein hydrolysates. , Porous materials, as the core of the adsorption approach, can efficiently capture peptides with specific properties by their surface and pore physical properties. Jiang and co-workers prepared Fe 3 O 4 @SiO 2 @graphene microspheres to enrich bioactive peptides at low concentrations with high efficiency.…”
Section: Introductionmentioning
confidence: 99%